Sepsis Biomarkers in Neonates and Children: C-Reactive Protein and Procalcitonin - Markic, J.; Saraga, M.; Dahlem, P. (Journal of Child Science, 2017)
Bacteremia and sepsis are still significant causes of morbidity and mortality among children and neonates worldwide. Early recognition of bacterial sepsis and initiation of therapy is associated with better treatment outcomes but is challenging as many of the early clinical features can be similar to those in self-limiting viral illnesses. Diagnosis of bacteremia is also challenging because the use of blood culture, the gold standard for diagnosis of bacteremia, is fraught with difficulties. Therefore, various biomarkers are of great importance in the process of diagnosis of sepsis and evaluation of its severity. They can indicate the presence or absence or severity of sepsis and are helpful in differentiating bacterial from viral and fungal infection. Of the many proposed biomarkers for infection and/or sepsis, acute-phase proteins such as C-reactive protein (CRP) and procalcitonin (PCT) are widely used and have perhaps been most widely assessed. In this review, we will present the advantages and disadvantages of CRP and PCT determination in sepsis evaluation. It will be presented that it is still not always possible to predict accurately the presence of bacterial infection on the basis of clinical appearance and available laboratory tests. Therefore, the investigation of new and better biomarkers is challenging and ongoing.
Keywords: sepsis; biomarker; C-reactive protein; procalcitonin